Endovascular robotic: feasibility and proof of principle for diagnostic cerebral angiography and carotid artery stenting. (1st March 2020) - Sajja, Kalyan Chekravarthy; Sweid, Ahmad; Al Saiegh, Fadi; Chalouhi, Nohra; Avery, Michael B; Schmidt, Richard F; Tjoumakaris, Stavropoula I; Gooch, Michael Reid; Herial, Nabeel; Abbas, Rawad; Zarzour, Hekmat; Romo, Victor; et al.
Abstract : Background: Robots in surgery aid in performing delicate, precise maneuvers that humans, with inherent physical abilities, may be limited to perform. The CorPath 200 system is FDA approved and is being implemented in the US for interventional cardiology procedures. CorPath GRX robotic-assisted platform is the next-generation successor of CorPath 200. Objective: To discuss the feasibility and early experience with the use of the CorPath GRX robotic-assisted platform for neuroendovascular procedures, including transradial diagnostic cerebral angiograms and transradial carotid artery stenting. Methods: The cases of 10 consecutive patients who underwent neuroendovascular robotic-assisted procedures between December 1, 2019 and December 30, 2019, are presented. Results: Seven patients underwent elective diagnostic cerebral angiography, and three patients underwent carotid artery angioplasty and stenting using the CorPath GRX robotic-assisted platform. All procedures were performed successfully, and no complications were encountered. Conversion to manual control occurred in three diagnostic cases because of a bovine arch that was previously not known. The fluoroscopy time and the procedure time continued to improve with subsequent procedures as we streamlined the workflow. Conclusion: This series demonstrates the early use of this technology. It could potentially be used in the near future for acute stroke interventions in remote geographic locations and in places where a neurointerventionalist is not available.